2014
DOI: 10.1136/bjophthalmol-2014-305300
|View full text |Cite
|
Sign up to set email alerts
|

Novel mitochondrial tRNAIlem.4282A>G gene mutation leads to chronic progressive external ophthalmoplegia plus phenotype

Abstract: We describe a novel MTTI transition mutation at nucleotide position m.4282G>A associated with a CPEO plus phenotype. The novel variant at position m.4282G>A disrupts the middle bond of the D-stem of the tRNA(Ile) and is highly conserved. The conservation and phenotype-genotype segregation strongly suggest pathogenicity and is in good agreement with the MTTI gene being frequently associated with CPEO. This novel variant broadens the spectrum of MTTI mutations causing CPEO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…So far, disease causing D-stem variants are reported for 16 of the 22 mt-tRNA genes, and are associated with a wide range of clinical presentations (Supplementary Table 1). Some of these mt-tRNA D -stem cases have a relatively low (18-38%) muscle mutation load and clearly show phenotypical overlap with our patient, displaying relatively mild symptoms (mainly CPEO, ptosis, myopathy) with an age of onset at 26-66 years [13][14][15][16][17] . As compared to other pathogenic variants in the tRNA Met gene (summarized in [18] ) our patient has a much lower muscle heteroplasmy level, probably responsible for the milder phenotype and later onset of disease than the other reported MT-TM patients.…”
Section: Discussionsupporting
confidence: 53%
“…So far, disease causing D-stem variants are reported for 16 of the 22 mt-tRNA genes, and are associated with a wide range of clinical presentations (Supplementary Table 1). Some of these mt-tRNA D -stem cases have a relatively low (18-38%) muscle mutation load and clearly show phenotypical overlap with our patient, displaying relatively mild symptoms (mainly CPEO, ptosis, myopathy) with an age of onset at 26-66 years [13][14][15][16][17] . As compared to other pathogenic variants in the tRNA Met gene (summarized in [18] ) our patient has a much lower muscle heteroplasmy level, probably responsible for the milder phenotype and later onset of disease than the other reported MT-TM patients.…”
Section: Discussionsupporting
confidence: 53%
“…A more convenient amplicon was obtained by SspI digestion for fragment analysis on an ABI3100 capillary sequencer. Standard RFLP by inclusion of a mismatch in the primer site (Jackson et al, 2014a) was feasible, since the patient also harboured the additional polymorphism m.8610T > C and m.8614T > C resulting in a homopolymeric cytosine stretch. Therefore, an approach by fragment analysis on a capillary sequencer to discriminate the C insertion from wild type sequence was used to calculate the heteroplasmic degree.…”
Section: Molecular Genetic Analysismentioning
confidence: 99%
“…Moreover, mitochondrial genome of diabetic subjects and one of three cases of hyperlipidemia, EGY7, EGY9, and EGY2 contained T16189C mutation (Table 2) associated with insulin resistance and type 2 diabetes mellitus [53,54,55,56]. Among the variants that were not related to obesity, we found that A4282G (Table 2) associated with chronic progressive external ophthalmoplegia (CPEO) was present in all samples [57]. Mutations (disease associated) EGY1 T195C, A4282G , A8108G), A10398G ,G15043A, G16129A), A16183C and T16189C EGY2 T4216C ,A4282G), A4917G), A10398A) and G15928A EGY3 T195C, A4282G , A10398G T15784C , G16390A and T16519T EGY4 T195C , A4282G , A10398G (, T15784C, G16390A and 16519 EGY5 A4282G , A10398G and G15043A EGY6 A4282G , A10398A ), T16093C and T16519T EGY7 T195C ), G3316A , A4282G, G9055A , A10398A , A11467G, A12308G , G12372A, G14831A , A16183C and T16189C EGY8 A4282G , A10398A ), C16192T and T16519T EGY9 T4216C , A4282G , A4917G , A10398A , G15928A and T16189C…”
Section: Mitochondrial Dna Analysismentioning
confidence: 87%